Internalization of Religious Values Through Religious Activities at MAN Klaten - Khoiriyah, Nurul Asma; Salim, Hakimuddin (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
This research discusses the internalization of religious values at MAN 1 Klaten through various religious activities aimed at instilling the values of faith, morality, and exemplary behavior in students. This internalization is carried out through daily activities such as prayer recitations, murojaah (qur'an memorization review), tadarus (qur'an recitation), congregational dhuha prayers, and the habit of greeting and handshaking. The study employs a qualitative approach with a phenomenological method to explore the meaning of the experiences of the informants related to the process of internalizing religious values. The results indicate that the role of teachers, the school environment, and habitual methods are the main factors in instilling religious values in students. Supporting factors come from teachers and parents, while the inhibiting factor is the lack of seriousness from students in carrying out religious activities. The internalization of these values aims to shape students' character to be virtuous and possess a religious ethos in their daily lives.